CASTING PRACTICE EQUIPMENTS TO IMPROVE STUDENTS’ LEARNING OUTCOMES - Mujiyono Mujiyono; Agung Pratama Putra (Jurnal Kependidikan, 2018)
This study was aimed at determining the effectiveness of metal casting practice equipement in improving student learning outcomes in metal casting practice from the cognitive aspects. This study used quasi-experimental method with pretest-posttest control group design. The population of this study were the students of class X Machine Engineering at vocational high school in Yogyakarta year 2016/2017. The samples were taken by random assignment method. The control group sample was class X TP 3 and the sample of the experimental group was class X TP 4. The data were collected using objective test instruments given before and after the treatment. The data analysis used in this study was descriptive statistics and parametric statistics using the T-test. The calculation of data analysis used SPSS v18 software. The results show that the media of metal casting practice tools is effective in improving student learning outcomes in the metal casting practice material from the cognitive aspects. This is indicated by the percentage of completeness of learning outcomes of students who use media casting metal casting tools by 75% while students who use the lecture method by 35.7%.PERANGKAT PRAKTIK PENGECORAN UNTUK MENINGKATKAN HASIL BELAJAR SISWAAbstrakPenelitian ini bertujuan untuk mengetahui efektivitas media perangkat praktik pengecoran logam dalam meningkatkan hasil belajar siswa pada materi praktik pengecoran logam dari aspek kognitif. Penelitian ini menggunakan metode kuasi eksperimen dengan desain pretest-posttest control group design. Populasi penelitian ini adalah siswa kelas X Teknik Pemesinan SMK di Yogyakarta Tahun Ajaran 2016/2017. Sampel diambil dengan cara random assignment. Sampel kelompok kontrol adalah kelas X TP 3 dan sampel kelompok eksperimen adalah kelas X TP 4. Data dikumpulkan menggunakan instrumen tes objektif yang diberikan sebelum dan sesudah pembelajaran.Analisis data yang digunakan adalah statistik deskriptif dan statistik parametris dengan uji-T. Perhitungan analisis data menggunakan software SPSS v18. Hasil penelitian menunjukkan bahwa media perangkat praktik pengecoran logam efektif dalam meningkatkan hasil belajar siswa pada materi praktik pengecoran logam dari aspek kognitif. Hal ini ditunjukkan dengan persentase ketuntasan hasil belajar siswa yang menggunakan media perangkat praktik pengecoran logam sebesar 75% sedangkan siswa yang menggunakan metode ceramah sebesar 35,7%.